Warunki rejestracji i zakres ochrony kompozycji kolorystycznej jako znaku towarowego w świetle przepisów krajowych oraz dyrektywy 2015/2436 - Sitko, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Pursuant to the provisions of the Act of 30 June 2000 on Industrial Property Law, combinations of colours may be considered as trademarks. This notion applies to trade marks which bear an arrangement of two or more colours per se. It is a specific category of denominations with respect to which detailed principles for the presentation thereof in a relevant register has been developed in the preliminary rulings of the European Court of Justice. It follows from the well-established jurisprudence of Polish and EU courts alike that in addition to the graphic presentation of a combination of colours, the description of the relevant trade mark in an application for trade mark protection plays a major role. Such a description should include, besides specifying the colour and its number in the international classification of colours, information on the fixed arrangement of colours that constitute the trade mark. Such requirements concerning the presentation of the trade mark in the register determine the scope of its protection. Despite the fact that the object of the application concerning a combination of colours is a contour-free arrangement of two or more colours, the actual protection is similar to that which is proper for the protection of graphic signs composed of colours enclosed in defined geometrical figures. The scope of protection of such a trade mark is strictly determined by indicating mutual relations between/among colours and the manner in which they are linked (e.g., straight line, undulating line, colour blur, etc.). Thus, a trade mark with a combination of colours is not subject to protection with respect to all possible arrangements of colours that make up a given trade mark. The considerations presented in this article also refer to the changes introduced in Directive (EU) 2015/2436 on the graphic representation of a trade mark and its effects on the presentation of trade marks which constitute a combination of colours. This issue is presented in the context of detailed guidelines that stem from the Commission Implementing Regulation (EU) 2017/1431 concerning the European Union trade mark.